The Biochemical Composition and Antioxidant Properties of Fucus vesiculosus from the Arctic Region - Ekaterina D. Obluchinskaya; Olga N. Pozharitskaya; Denis V. Zakharov; Elena V. Flisyuk; Inna I. Terninko; Yulia E. Generalova; Irina E. Smekhova; Alexander N. Shikov (Marine Drugs, 2022)
Fucus vesiculosus is one of the most prominent brown algae in the shallow waters of the seas of the Arctic region (Barents (BS), White (WS), Norwegian (NS), and Irminger (IS)). The aim of this study was to determine the biochemical composition of F. vesiculosus from the Arctic at different reproductive phases, and to evaluate the antioxidant properties of F. vesiculosus extracts. The amounts of monosaccharides, phlorotannins, flavonoids, and ash and the mineral composition significantly varied in the algae. A strong correlation was established between monosaccharide, phlorotannin, and flavonoid accumulation and water salinity (Pearson’s correlation coefficients r = −0.58, 0.83, and 0.44, respectively; p < 0.05). We noted a negative correlation between the antioxidant activity and the amount of the structural monosaccharides of fucoidan (r = −0.64). A positive correlation of phlorotannins and flavonoids with antioxidant power was confirmed for all samples. The ash accumulation was relatively lower in the sterile phase for the algae from the BS and WS. The correlation between the Metal Pollution Index (MPI) and the reproductive phases was medium with high fluctuation. Meanwhile, the MPI strongly correlated with the salinity and sampling site. The gradient of the MPI values across the sea was in the following ranking order: BS < WS < NS < IS. Taken together, and based on our data on the elemental contents of F. vesiculosus, we believe that this alga does not accumulate toxic doses of elements. Therefore, the Arctic F. vesiculosus could be safely used in food and drug development as a source of active biochemical compounds and as a source of dietary elements to cover the daily nutritional requirements of humans.